Extension of the School Day and the Third Sector: the role of CENPEC - Regis Eduardo Coelho Argüelles da Costa (Universidade Federal do Rio Grande do Sul, 2018)
The article analyzes the development and dissemination of proposals for expand the school day by the Centro de Estudos e Pesquisas em Educação, Cultura e Ação Comunitária (CENPEC) from 1993 to 2006. We seek to the propositions, and persuasion strategies used along the civil and politic society, from various documents signed by the NGO and its intellectuals. Next, we evaluate the assimilation of this set of propositions by Programa Mais Educação, school day expansion policy of the Federal Government, since 2007.